Partisipasi Perempuan Dalam Program CSR Masyarakat Sobokerto Peduli Waduk Cengklik (Mas Sopili) Binaan PT Pertamina Patra Niaga DPPU Adi Sumarmo - Ananta Ria Safitri; Siti Fatonah; Bintang Fajar Pamungkas (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Gender inequality is still a problem faced by Indonesian society, so efforts are needed to realize gender equality, one of which is through empowering women. PT Pertamina Patra Niaga DPPU Adi Sumarmo through the Sobokerto Community Cares for Cengklik Reservoir (Mas Sopili) program is trying to involve women through the formation of the Ngudi Makmur Women's Farmer Group (KWT) and KWT Bangun Sejahtera. In empowerment activities, participation is the key to determining the success of the program. This research aims to analyze women's participation in the Mas Sopili program. The research method used is descriptive qualitative research using primary and secondary data. The research results show that KWT members actively participate in various stages of activities, namely the planning, implementation, enjoying the results and evaluation stages. The form or type of participation provided is in the form of thought, energy, skills, goods, and money. There are factors inhibiting community participation in this activity, namely availability of time, lack of increase in income, and lack of motivation and awareness. Meanwhile, the driving factor is member motivation and encouragement from the chairman of each KWT.